2021
DOI: 10.3389/fonc.2021.617179
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Reorganization of Language Network Modules in Glioma Patients: New Insights From Resting State fMRI Study

Abstract: BackgroundPrior investigations of language functions have focused on the response profiles of particular brain regions. However, the specialized and static view of language processing does not explain numerous observations of functional recovery following brain surgery. To investigate the dynamic alterations of functional connectivity (FC) within language network (LN) in glioma patients, we explored a new flexible model based on the neuroscientific hypothesis of core-periphery organization in LN.MethodsGroup-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In particular, the first applications of deep learning methods have been showing that such an approach can achieve excellent outcomes for the specific purpose of reconstructing tb-fMRI-like networks, starting from the rs-fMRI data. Nevertheless, it is also significant to note that ICA is already widely acknowledged, so much so that it is also used to isolate the functional networks in studies that do not focus on their identification but rather aim at characterizing their properties in terms of FC [29][30][31][32].…”
Section: Language Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the first applications of deep learning methods have been showing that such an approach can achieve excellent outcomes for the specific purpose of reconstructing tb-fMRI-like networks, starting from the rs-fMRI data. Nevertheless, it is also significant to note that ICA is already widely acknowledged, so much so that it is also used to isolate the functional networks in studies that do not focus on their identification but rather aim at characterizing their properties in terms of FC [29][30][31][32].…”
Section: Language Networkmentioning
confidence: 99%
“…The language network is reported to undergo an overall reduction in the FC [29] and network strength [42] in patients affected by gliomas, which was also observed to be associated with the tumor grade [42]. Interestingly, such alterations showed differences based on whether the lesion was located in the left or the right hemisphere: in the former case, the FC reduction emerged within both the hemispheres bilaterally [29], in particular between the Broca and Wernicke areas [43], whereas in the latter case, significantly lower values were observed only in the ipsilateral hemisphere [29]. In contrast to this, another research study, focusing on temporal gliomas, found that the LN only showed lower integration and higher segregation properties in the case of right-sided tumors, whereas those in the left mainly affected the visual network (VN) [44,56].…”
Section: Language Networkmentioning
confidence: 99%
“…In studies investigating the LANG, an overall decrease of rs-FC 14,15 as well as network strength 16 in patients compared to healthy controls was reported.…”
Section: Introductionmentioning
confidence: 98%
“…While most of these studies have focused their attention on speci c RSNs, such as language network (LANG) [14][15][16] , default-mode network (DMN) 12,[17][18][19][20][21] and fronto-parietal network (FPN) [16][17][18] , only a few number of papers have investigated these alterations at the whole-brain level 19,[22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Resting state fMRI on the other hand is a technique, believed to depend on the neurovascular uncoupling causing changes in neurometabolites. Language network studies done using resting state (rs) fMRI have shown differences in the network organization before and after surgery in glioma patients ( Deverdun et al, 2020 ), and also, there is literature on the extent of the network involved in language function even in the contralateral hemisphere although impacting the core network to a lesser extent ( Jin et al, 2021 ). MEG studies has reported that FC network alterations in the theta, alpha, and gamma bands are associated with poorer performance on a verbal fluency test in glioma patients ( Van Dellen et al, 2012 ; Hu et al, 2013 ; Derks et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%